Modeling cyclic behavior of clay subjected to principal stress rotation. (October 2022) - Du, Zibo; Yin, Zhen-Yu; Qian, Jiangu; Guo, Yuancheng; Huang, Maosong
Abstract: Experimental evidence indicates that principal stress rotation yields complex cyclic behavior in clay, which is significant in many cases but not adequately described by constitutive modeling. To address this issue, a constitutive model was developed to describe the cyclic behavior of clay within the framework of bounding surface elastoplasticity. To describe the plastic mechanism induced during reversal loading, the mapping rules for the relocatable projection center were formulated in the deviatoric stress space, which are also applicable to pure principal stress rotation. The effects of small strain stiffness and anisotropic elasticity were incorporated into the model to describe cyclic degradation and plastic accumulation behavior under principal stress rotation. To describe the non-coaxiality, a three-dimensional non-coaxial flow rule was incorporated into the model. It was assumed to be colinear with a non-coaxial stress rate orthogonal to a reference stress tensor and dependent on the stress ratio. The developed model was validated against the undrained hollow cylindrical torsional shear tests subjected to cyclic pure principal stress rotation for Shanghai and Hangzhou clay with various intermediate principal stress coefficients. The comparison between simulations and experimental results demonstrates that the proposed model can model the cyclic behavior of clay subjected to principal stress rotation.